Re-Scaling of Metropolitan Governance in Germany - Karsten Zimmermann (Raumforschung und Raumordnung, 2017)
Germany lacks a systematic nation-wide approach for the governance of metropolitan regions. We observe a considerable variety of institutional solutions for the governance of metropolitan affairs. In particular since the 1990s many initiatives have blossomed at different scales giving different weight to economic development, infrastructure planning, spatial planning or waste management. Therefore, the German federal state can be seen as a laboratory for metropolitan governance with a few outstanding cases and some less successful ones. However, the current situation calls for more effective metropolitan governance in most of the German metropolitan regions. The article gives an historical overview, describes recent trends and illustrates four cases in more detail. The emergence of multi-scaled arrangements where different forms of governance function on different spatial scales seems to be the most recent pattern in Germany. The outlook remains unclear.